Ag–Cu nanoparticles as efficient catalysts for transesterification of β-keto esters under acid/base-free conditions. Issue 23 (16th February 2016) - Yue, Hongmei; Yu, Hao; Liu, Sheng; Xu, Chunli
Abstract : For the first time transesterification of β-keto esters, conventional acid- or base-catalyzed reactions, has been catalyzed by Ag–Cu bimetallic nanoparticles with high activity. Abstract : Transesterification of β-keto esters and alcohols are traditionally catalyzed by acid or basic catalysts. However, these traditional catalysts do not always meet the requirements of modern synthetic chemistry which need to be highly efficient, selective, and environmentally friendly. In this work, Ag–Cu metal sites were first introduced as transesterification catalysts. The effect of the support, Ag : Cu molar ratio, and reaction conditions were investigated. The Ag–Cu metal sites were proved to be active in the β-ketoester transesterification with various alcohols, having yields comparable to the conventional acid- or base-catalysts.